Electromagnetic shielding properties of carbon fibre reinforced cementitious composites. (10th November 2020) - Wanasinghe, Dimuthu; Aslani, Farhad; Ma, Guowei
Highlights: CFs enhance flexural strength in cementitious composites. Electrical conductivity increases and reaches a saturation level with CF loading. EMI shielding is better in composites with unsized CF compared to desized CFs. EMI shielding increases with the unsized CF loading and length. Abstract: The need for construction materials with high electromagnetic (EM) shielding properties is growing globally due to the rapid development of electronic devices. This study has aimed at fabricating a cement-based composite that could be developed for electromagnetic shielding applications within the industry. To impart EM shielding properties, unsized carbon fibres with lengths of 3 mm, 6 mm, and 12 mm and desized carbon fibres with lengths of 6 mm and 12 mm were mixed to a control mix. Different weight fractions of 0.1%, 0.3%, 0.5%, and 0.7% of carbon fibres of each type were used in the fabrication of specimens. Each mix was subjected to mechanical, electrical conductivity, electromagnetic interference shielding, and scanning electron microscope analyses for characterisation. Results show that the addition of carbon fibres has a significant improvement in flexural, electrical conductivity, and electromagnetic interference shielding properties. The mix with the highest electrical conductivity was the one with unsized 12 mm carbon fibres with a weight fraction of 0.7%. The same mix showed the best electromagnetic interference shielding properties, which was about 40–60 dB within 300 MHz to 1.5 GHz frequency range. Comparison of obtained results with mixes reported in the literature containing carbon within a cement matrix showed that electromagnetic interference shielding performance of the best mix in this study exceeded performance reported in the literature for the same frequency range.